Surgical Outcome Of Spontaneous Intracerebral Haematoma Through Keyhole Craniectomy - Hossain, M; Ahmed, SU; Ansary, SAA; Islam, SMK (Faridpur Medical College Journal, 2011)
Management of spontaneous intracerebral haematoma (SICH) is divided into two groups - medical and surgical interventions. Although surgical management is controversial, it can be life saving when patient is deteriorating. Surgical techniques varies from large craniotomy, burr hole aspiration, stereotactic & endoscopic evacuation of haematoma. Forty eight patient of SICH were treated surgically using keyhole craniectomy technique, small craniectomy of 2-2.5 cm diameter. Surgical outcome assessed by Glasgow Outcome Score (GOS). Post-operative CT scan was done in all cases. Good recovery was achieved in 2 cases (4%), moderate disability in 20 cases (42%), 5 patients remain in vegetative state. Good evacuation of haematoma was seen in 42 patients except 6 cases deteriorated by post-operative CT scan. Surgical evacuation of SICH through keyhole technique is minimally invasive, safe and can achieve desired result. Patient with a GCS > 9 prior to surgery demonstrate a better outcome with this minimally invasive method. DOI: 10.3329/fmcj.v5i2.6824 Faridpur Med. Coll. J. 2010;5(2):60-62